Ever at the ready for events that never happen - Jos F. Brosschot (European Journal of Psychotraumatology, 2017)
Stress, whether daily stress, work stress or traumatic stress, is unhealthy. This lecture covers three recent theoretical approaches in explaining the mechanisms underlying the influence of psychological stress on somatic health. It is argued that stress research should focus less on stressors themselves and put more emphasis on prolonged stress responses. Three mechanisms are identified that cause this unhealthy prolonged stress response: first, the partly-proven mechanism of perseverative cognition; second, the mechanism of unconscious stress, which is currently being explored; and third, the notion of the stress response being a default response that is inhibited only when safety is perceived. All three mechanisms are deeply rooted in millions of years of our evolution. Although the dangers of the past have virtually disappeared, many of us remain ever at the ready for events that never happen.